Micromechanics of agglomeration forced by the capillary bridge: The restitution of momentum. Issue 11 (21st June 2013) - Balakin, Boris V.; Alyaev, Sergey; Hoffmann, Alex C.; Kosinski, Pawel
<x xml:space="preserve">Abstract</x> The formation of capillary bridge formed by a liquid adsorbate is one of the main reasons for agglomeration in multiphase flows. Agglomeration takes place when the relative momentum of two colliding particles is fully consumed by the bridge. This article presents a theoretical study of the collisions of particles with adsorbed liquid taking into account the influence of capillary and viscous dissipative forces. The article proposes an approximate analytical solution for the dynamics of the bridge formed during the collision, together with a more complete numerical model, which is validated with experimental data. The restitution of the relative momentum of the colliding particles, depending on a series of dimensionless parameters characterizing the bridge, is investigated. A criterion for prediction of agglomeration, or "collision efficiency, " in a flow involving cohesive particles is given. An expression is proposed for the coefficient of restitution for the case of collision via a liquid bridge. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4045–4057, 2013